Description Option and their Impact on Netting Contracts in the 'Sell and Lease' Model - Abu Yahia, Ali Abdallah (Dirasat: Shari'a and Law Sciences, 2023)
Objectives: This study aims to explain and clarify the provisions of the option to waive the description requirement and its impact on netting contracts, specifically in the context of the lease and sale field. This will be achieved by identifying the relevant sections pertaining to this option and its impact on the necessity of sale and lease contracts. Methods: The study used an inductive method to gather relevant scientific material from different sources necessary for this research. It also employed an analytical approach by presenting the doctrines of jurisprudence, clarifying their evidence, and discussing and indicating any evidence to determine what appears to be correct based on the evidence. Results: The study concludes that the foundation of contracts is reliability and necessity, and the option to waive the description requirement is incidental and used to address special situations. The buyer and lessee are entitled to compensation for the loss of the desired description of the goods sold or leased entity if they consented to the contract's signing and did not use their right of avoidance. Conclusions: The study recommends conducting further research on the impact of the loss of the description option on non-sale and lease netting contracts, such as Istisna'a and Salam sales that have their unique provisions. These contracts may have special provisions that differ from the general sales provisions.